Sex museum: Fly by night. Live at Caracol (Locomotiv music, 2004)
Tracklist: 01. Minnesota strip. 02. Two sisters. 03. Collectors. 04. Red ones. 05. Lets go out. 06. Last last. 07. Get lost. 08. Where I belong. 09. Empty's my soul. 10. I walk alone. 11. Messing with you. 12. Jet Sam. 13. We can move. 14. Landlors. 15. Street fight. 16. Whole lotta Rosie. 17. Flying' high. 18. Speedkings. 19. Start to move. 20. I'm free.